2018
DOI: 10.1002/14651858.cd001261.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines for preventing typhoid fever

Abstract: Background Typhoid fever and paratyphoid fever continue to be important causes of illness and death, particularly among children and adolescents in south‐central and southeast Asia. Two typhoid vaccines are widely available, Ty21a (oral) and Vi polysaccharide (parenteral). Newer typhoid conjugate vaccines are at varying stages of development and use. The World Health Organization has recently recommended a Vi tetanus toxoid (Vi‐TT) conjugate vaccine, Typbar‐TCV, as the preferred vaccine for all ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 95 publications
(176 reference statements)
1
72
0
13
Order By: Relevance
“…Two-year post-vaccination effectiveness was87% [36,43]. A single randomized trial in Indian children aged between six months and 12 years did not clarify the efficacy of two doses of Vi-TT vaccine one year after administration [40].A real-life survey in Germany described an adverse event rate of 28.6% (fatigue, pain, headache, pyrexia, myalgia, and swelling), increased after concomitant immunization with other vaccines(i.e., rabies, typhoid, and yellow fever vaccines) [44].A US military study showed more adverse events in individuals exposed to the polysaccharide Vi vaccine in comparison with those exposed to the oral vaccine, although rash and diarrhea were more incident in the latter group [45].Fever and pain at the injection site were incident using parenteral vaccines [40].…”
Section: Vaccination Status In Travelersmentioning
confidence: 99%
See 2 more Smart Citations
“…Two-year post-vaccination effectiveness was87% [36,43]. A single randomized trial in Indian children aged between six months and 12 years did not clarify the efficacy of two doses of Vi-TT vaccine one year after administration [40].A real-life survey in Germany described an adverse event rate of 28.6% (fatigue, pain, headache, pyrexia, myalgia, and swelling), increased after concomitant immunization with other vaccines(i.e., rabies, typhoid, and yellow fever vaccines) [44].A US military study showed more adverse events in individuals exposed to the polysaccharide Vi vaccine in comparison with those exposed to the oral vaccine, although rash and diarrhea were more incident in the latter group [45].Fever and pain at the injection site were incident using parenteral vaccines [40].…”
Section: Vaccination Status In Travelersmentioning
confidence: 99%
“…Ty21a live attenuated vaccine, developed from attenuated Ty2 strains of S. typhi, does not confer protection after a single dose; three doses administered in alternate days in persons living in endemic countries and four doses in travelers are usually recommended to elicit adapted mucosal immunity (IgA antibodies), whose duration lasts~7 years in 60-70% of the vaccinated cases [38,39]. Half of typhoid fever cases could be prevented until three years after vaccination [40].…”
Section: Vaccination Status In Travelersmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, invasive NTS bacteremia (iNTS) is a common complication observed in immunocompromised adults and in young children with severe malaria and malnutrition (4). The current available licensed vaccines against Salmonella are the oral live attenuated Ty21a, the Vi capsular polysaccharide (Vi CPS), and the Vi-tetanus toxoid conjugate (Vi-TT), which only target the Typhi serovar, and have shown variable efficacy; 50% (95% CI 35-61%) for Ty21a, 55% (95% CI 30-70%) for Vi-CPS, and 54.6% (95% CI 26.8-71.8%) for Vi-TT (5,6), while no licensed vaccines against iNTS are currently available (7). Although cross-reactivity through vaccination with the Ty21a vaccine can be induced against Paratyphi A, B, and Enteritidis serovars (8,9), cross-protection has been reported only against Paratyphi B (10).…”
Section: Introductionmentioning
confidence: 99%
“…It remains a considerable global health challenge, causing an estimated 14.3 million (12•5-16•3) infections and 136 000 deaths annually 1 . Until recently 2 , licensed vaccines for S. Typhi were only moderately efficacious 3 and could not be used in young children. There are currently no licensed vaccines for S. Paratyphi 4 .…”
Section: Introductionmentioning
confidence: 99%